On Peter Singer - Hochsmann, Hyun (Wadsworth/Thomson Learning, 2002)
This brief text assists students in understanding Singer's philosophy and thinking so they can more fully engage in useful, intelligent class dialogue and improve their understanding of course content. Part of the Wadsworth Notes Series, (which will eventually consist of approximately 100 titles, each focusing on a single "thinker" from ancient times to the present), ON SINGER is written by a philosopher deeply versed in the philosophy of this key thinker. Like other books in the series, this concise book offers sufficient insight into the thinking of a notable philosopher, better enabling students to engage in reading and to discuss the material in class and on paper